Individual’s Characteristics and Ethical Financial Reporting Choice - Rahayu, Yunita Dwi; Chariri, Anis (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2016)
The aim of this study is to examine the influence of individuals’ characteristics such as cognitive moral development, idealism, machiavellianism, deontology, and risk preference on the ethical financial reporting choice. The accountant profession cannot be separated from many ethical considerations that have been set with the professional ethics, and the professional ethics will be closely related with the individuals to consider how far they have applied those professional ethics, thus this research aims to identify whether the individuals’ characteristics influence the ethical financial reporting choice. This research is expected to be an important reference in the development of accounting knowledge particularly that which is related with the ethical-based financial reporting. Total sample of 56 respondent were used for this study. Primary data gained through questionnaires were analyzed using logistic regression model. The findings of this study showed that risk preference had negatively significant influence on ethical financial reporting choice, while cognitive moral development, idealism, machiavellianism, and deontology had no significant effect on ethical financial reporting choice.